STRATEGI DAN TEKNI KADTUSTMEN TRADING OPTIONS UNTUK PASAR YANG TIDAK BERARAH (DIRECTIONLESS MARKET) PADA PASAR AMERIKA STUDI UNDELYING STOCK, ETF DAN INDEX - , Moch Arifin; , Dr. Sumiyana, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Options is a derivative financial product as it has underlying assets. They can be either stocks, index, currency or ETF (Exchange Trade Fund). The options is a contract between buyer and seller towards underlying assets which have a fixed price at specific date. As options buyers or Long Call Options they have right not obligation to buy underlying assets at a fixed price before expiration. As of the right they must pay options premium to the seller. As options seller or Short Call Options they have obligation to deliver the underlying assets to the buyer as of the buyer exercised the right, it means the seller is assigned by the buyer. Another type of options is Put Options. As options buyer or Long Put Options they have right not obligation to sell underlying assets at a fixed priced before expiration. As of the right they must pay options premium to the seller. As options seller or Short Put Options they have obligation to buy underlying assets as the buyer exercised the right, it means the seller is assigned by the buyer. The main goal of the research is to find out for options trading strategy especially for underlying assets of Index, stocks and ETF in three types of financial market condition i.e. bullish, bearish and sideways. Another goal is to implement adjustment technique strategy when the prediction of market condition is different with initial assumption. Using adjustment strategy expected to reduce of potential loss even to make profit when the adjustment is suitable with market tendency. The market data of the underlying assets between 2010 to 2012 derived from options brokerage named Thinkorwim. To analyze whether the returns of options trading for the underlying assets gave the same result or not, testing to use ANOVA one direction will be applied to analyze it in the same condition of strategy type of options trading and the date. Time expiration for al trading will be applied approximately one month long, and the trading will be closed at that month whether using adjustment strategy or not.